The Synergistic Effect of High Pressure CO2 and Nisin on Inactivation of Bacillus subtilis Spores in Aqueous Solutions - Rao, Lei; Wang, Yongtao; Chen, Fang; Liao, Xiaojun (Frontiers in Microbiology, 2016)
The inactivation effects of high pressure CO2 + nisin (simultaneous treatment of HPCD and nisin, HPCD + nisin), HPCD→nisin (HPCD was followed by nisin), and nisin→HPCD (nisin was followed by HPCD) treatments on Bacillus subtilis spores in aqueous solutions were compared. The spores were treated by HPCD at 6.5 or 20 MPa, 84–86°C and 0–30 min, and the concentration of nisin was 0.02%. Treated spores were examined for the viability, the permeability of inner membrane (IM) using flow cytometry method and pyridine-2, 6-dicarboxylic acid (DPA) release, and structural damage by transmission electron microscopy. A synergistic effect of HPCD + nisin treatment on inactivation of the spores was found, and the inactivation efficiency of the spores was HPCD + nisin > HPCD→nisin or nisin→HPCD. Moreover, HPCD + nisin caused higher IM permeability and DPA release of the spores than HPCD. A possible action mode of nisin-enhanced inactivation of the spores was suggested as that HPCD firstly damaged the coat and cortex of spores, and nisin penetrated into and acted on the IM of spores, which increased the damage to the IM of spores, and resulted in higher inactivation of the spores.